Development and characterization of nanosuspensions of olmesartan medoxomil for bioavailability enhancement - Hetal Paresh Thakkar; Bindesh Vishnubhai Patel; Sneha Piyush Thakkar (Wolters Kluwer Medknow Publications, 2011)
Background : Olmesartan medoxomil (OLM), an anti-hypertensive agent administered orally has absolute bioavailability of only 26% due to the poor aqueous solubility (<7.75 μg/ml). The present investigation aimed at enhancing the oral bioavailability of OLM by improving its solubility and dissolution rate by preparing nanosuspensions. Materials and methods : The nanosuspensions of OLM were prepared using media milling technique followed by its lyophilization using mannitol as a cryoprotectant. Various formulation as well as process parameters were optimized in order to achieve desirable size and saturation solubility. Characterization of the prepared nanosuspension was done with respect to particle size, zeta potential, saturation solubility, dissolution rate, morphology study (TEM), in-vitro and exvivo drug diffusion study. Evaluation of the crystalline state before and after particle size reduction was done by differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD). Results : The results indicated that the initial crystalline state is preserved following particle size reduction and that the saturation solubility, dissolution velocity and diffusion rate of the drug from the nanosuspension is significantly higher than that of the plain drug suspension as well as from the marketed tablet formulation. Conclusion : Nanosuspension seems to be a promising approach for bioavailability enhancement because of the simple method of its preparation and its universal applicability.